Conflicts with multiple battlefields - Dan Kovenock; Brian Roberson (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper examines conflicts in which performance is measured by the players' success or failure in multiple component conflicts, commonly termed 'battlefields'. In multi-battlefield conflicts, behavioral linkages across battlefields depend both on the technologies of conflict within each battlefield and the nature of economies or diseconomies in how battlefield out-comes and costs aggregate in determining payoffs in the overall conflict.
Keywords: C72; D74; H56; 330; conflict; contest; battlefield; Colonel Blotto Game; auction; lottery; Konflikt; Extensives Spiel; Auktionstheorie; Glücksspiel; Theorie